2022
DOI: 10.1039/d2sc01108e
|View full text |Cite
|
Sign up to set email alerts
|

Parallel imaging of coagulation pathway proteases activated protein C, thrombin, and factor Xa in human plasma

Abstract: Using a collection of natural and unnatural amino acids, we synthesized a set of fluorescent activity-based probes for the fast, direct, and simultaneous detection of coagulation factors in human plasma.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(19 citation statements)
references
References 73 publications
0
19
0
Order By: Relevance
“…Previous studies reported that the fXIa S1 pocket is wide, deep, highly conserved and able to interact exclusively with positively charged arginine, 7,30,31 which is also observed in the case of other serine proteases from the coagulation cascade. 33 We found that in addition to arginine, the fXIa S1 subsite could also accommodate an unnatural phenylalanine derivative with a guanidine group in the para position, that is, L-Phe(guan) and several other amino acid residues (mostly phenylalanine derivatives). Our HyCoSuL screening showed that fXIa exhibited extremely narrow substrate specificity at the P2 position.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
See 3 more Smart Citations
“…Previous studies reported that the fXIa S1 pocket is wide, deep, highly conserved and able to interact exclusively with positively charged arginine, 7,30,31 which is also observed in the case of other serine proteases from the coagulation cascade. 33 We found that in addition to arginine, the fXIa S1 subsite could also accommodate an unnatural phenylalanine derivative with a guanidine group in the para position, that is, L-Phe(guan) and several other amino acid residues (mostly phenylalanine derivatives). Our HyCoSuL screening showed that fXIa exhibited extremely narrow substrate specificity at the P2 position.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
“…Protein C, factor X, and prothrombin were purified from fresh frozen plasma and then activated as previously described. 33 Expression and Purification of Recombinant Human Factor XI. Full-length cDNA for human factor XI was ligated into the cloning site of a mammalian expression vector (pCEP4) containing the cytomegalovirus promoter.…”
Section: ■ Discussion and Conclusionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tert -butyl ester group was easily hydrolyzed by trifluoroacetic acid (TFA), yielding 4a and 4b . On the basis of the structure of the previously obtained thrombin-selective substrate 36 we designed two fluorescent activity-based probes, namely, 5a and 5b , that contained fluorophores 4a and 4b , respectively, and one reference biotin-labeled probe 5c that contained a commercially available biotin tag. First, using the solid-phase approach, a recognition element was synthesized by elongating the peptide on 2-chlorotrityl resin.…”
mentioning
confidence: 99%